PURSUIT OF TIME AND MONEY : step into radical abundance and discover the secret to a meaningful prosperous life. - Spano, Sharon L. ([Place of publication not identified] : MORGAN JAMES Publishing, 2017)
The Pursuit of Time and Money explores the relationship between time and money and how those hidden dimensions impact perspectives and choices. The goal is to help people in business transform their relationship with time and money so they can let go of fear and scarcity and experience a more meaningful and prosperous experience of life. Sharon Spano explores the paradox of time and money from a human developmental lens that supports people in transformational change.
Intro -- Title -- Copyright -- Contents -- Acknowledgements -- Introduction: The Chase -- Part I: The Challenge: Developing Awareness of Your Thoughts and Behaviors -- 1 The Relationship Between Time and Money -- 2 Why What You Think About Time and Money Matters -- 3 The Paradox of Time and Money -- Part II: The Vision: Letting Go of the Fear -- 4 Time and Money as a Window into Your Soul -- 5 Scarcity Beliefs About Money -- 6 Scarcity Beliefs About Time -- Part III: The Opportunity: Stepping into Your Biggest Life -- 7 Be The Director of Your Own Movie -- 8 Pursue Time and Money in Healthier Ways -- 9 Understand Your Developmental Perspective -- 10 Trek the Path to Freedom -- Part IV: The Solution: Shifting to a Paradigm of Radical Abundance -- 11 A New Perspective on Money -- 12 A New Perspective on Time -- 13 The Secret to a Meaningful, Prosperous Life -- 14 Living in the Cycle of Freedom™ -- 15 Loving From Radical Abundance -- About the Author -- Appendix A -- Appendix B -- Appendix C -- Appendix D -- Bibliography -- Endnotes.
eBooks on EBSCOhost
Keywords: Finance, Personal; Time management; Success; Wealth; Conduct of life; Time Management; Achievement; Gestion du temps; Succès.; Richesse; Morale pratique; wealth; ethics (philosophical concept); Conduct of life; Finance, Personal; Success; Time management; Wealth